2010
DOI: 10.1152/ajprenal.00360.2010
|View full text |Cite
|
Sign up to set email alerts
|

PTH increases FGF23 gene expression and mediates the high-FGF23 levels of experimental kidney failure: a bone parathyroid feedback loop

Abstract: Parathyroid hormone (PTH) and fibroblast growth factor 23 (FGF23) target the kidney to cause a phosphaturia. FGF23 also acts on the parathyroid to decrease PTH expression, but in chronic kidney disease (CKD) there are high-serum PTH and FGF23 levels and resistance of the parathyroid to FGF23. We now report that PTH acts on bone to increase FGF23 expression and characterize the signal transduction pathway whereby PTH increases FGF23 expression. Remarkably, we show that PTH is necessary for the high-FGF23 levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
276
5
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 399 publications
(309 citation statements)
references
References 48 publications
22
276
5
6
Order By: Relevance
“…Both animal and human studies have shown that PTH administration increases FGF-23 (6-10), supporting the hypothesis that PTH is an important regulator of FGF-23. Reductions in PTH after parathyroidectomy have been associated with reductions in FGF-23 in animals with experimental renal failure and patients with ESRD (7,23,24). Therefore, it is plausible that reducing PTH concentrations with medical intervention in patients with SHPT might directly result in reductions in FGF-23 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Both animal and human studies have shown that PTH administration increases FGF-23 (6-10), supporting the hypothesis that PTH is an important regulator of FGF-23. Reductions in PTH after parathyroidectomy have been associated with reductions in FGF-23 in animals with experimental renal failure and patients with ESRD (7,23,24). Therefore, it is plausible that reducing PTH concentrations with medical intervention in patients with SHPT might directly result in reductions in FGF-23 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…25 Similarly, through use of a murine adenine/high PO4 diet model of CKD, it was reported that prior parathyroidectomy abrogated the CKD and hyperphosphatemia-induced increase in plasma FGF-23 concentration. 30 PTH, via PTH receptor1 (PTHR1) activation, is reported to increase murine osteocyte FGF-23 expression in vitro and to increase murine plasma FGF-23 concentration via a PTHR1 ligand (e.g., PTH) or constitutive activation of PTHR1. 31 Similarly, in humans potent PTHR1-mediated increases in plasma FGF-23 concentration have been demonstrated in Jansen metaphyseal chondroplasia, a disorder characterized by constitutive activating mutations in PTHR1.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 FGF23 reduces the 1,25-dihydroxyvitamin level by inhibiting the renal 1-a-hydroxylase expression and promoting the 24-hydroxylase expression, thereby downregulating the amount of phosphate absorption from the gut and resorption from the bone. 21,22 Mutual regulation of FGF23 and parathyroid hormone has been reported in rodent models 23,24 and identified in clinical cases of hypophosphatemic rickets and chronic kidney disease. 25 In addition to these systemic and hormonal patterns of regulation, the FGF23 expression appears to be regulated locally by FGF23-producing cells and osteocytes through molecules such as dentin matrix protein-1 (DMP1) 26,27 and the phosphate-regulating gene with homology to endopeptidases on X chromosome (PHEX), 28 both of which are highly expressed in osteocytes.…”
Section: Introductionmentioning
confidence: 99%